Seguidor solar de movimiento azimutal para concentrador solar híbrido (2023)
A compound parabolic concentrator was developed at UAN that currently concentrates static solar energy and does not present greater efficiency in energy collection, for which, it is required to design a mechanism that allows tracking the zenith and azimuthal movement of the sun in order to maximize the direct energy emitted by it and obtain a greater amount of energy collected.